Social media smartphone app and psychopathology – A case report - Santosh Kumar; Kavitha Natrajan; Ajeet Singh Bhadoria; Annya Das (Journal of Family Medicine and Primary Care, 2019)
Thought circulation in social media has always been contributed to psychological morbidity among youth. Although social media smartphone makes a comfort communication among generation it is also responsible for causing psychopathology among youth by circulating video depicting violent scene. The symptoms are often severe and persistent enough to have a significant impact on the person's day-to-day life. The purpose of this case report is to study the impact and consequences of social media (WhatsApp) on the mental health and stability among younger generation. A 30-year-old male patient presented at Family Medicine outpatient department with phobic and anxiety symptoms after witnessing a car accident in WhatsApp video which shows transaction of human body. His clinical presentation, management approach, and details of treatment are presented.